PENERAPAN PENGENDALIAN KUALITAS PRODUK JENDELA ALUMUNIUM DENGAN METODE SIX SIGMA DI PT YKK AP INDONESIA - Rusmalah; Ismi Mashabai (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2023)
PT. YKK AP Indonesia is a company that produces aluminum sills for apartments, housing, hotels, malls, and offices. Its main products are extruded aluminum finished goods in the form of windows, doors, and curtain walls, apart from storefront aluminum bar profiles. The problem at PT YKK AP Indonesia is a large number of defects in aluminum window products. It can be seen that the types of defects are dominated by scratch defects that exceed the level of disability, which is 2.83%, where the defect limit is 2%. With the high defects in the product, the researchers focused on repairs on the highest cause of damage to aluminum window products, namely scratch defects to measure and carry out quality improvements to reduce them by using DMAIC (Define, Measure, Analyze, Improve, Control) on Six Sigma. This method is relevant to find out the factors that cause the biggest defective products so that corrective action can be taken as soon as possible to reduce the number of defective products. Based on the results of quality measurements on six sigma products using DMAIC calculations, an average DPMO value of 8,748.937 was obtained with an average sigma value of 3.88 sigma, which is at the sigma level of Indonesian companies. However, this value still has the opportunity to be increased to reach a value of 6 sigmas or achieve zero defects on par with world-class industries. The repair strategy is carried out by implementing preventive maintenance and repairing worn machine parts, adding protection to aluminum windows, and adding light to the production area.